Strategic management paper For Tri Ocean Textile Co., Ltd. - Zhuo, Fei (Animo Repository, 2006)
The trade of textile products is the main source of foreign exchange earnings in Taiwan and plays an important role in Taiwan economic development. Tri Ocean Textile Co. Ltd. was founded in 1968 in Kuaishan Industrial Park as a PTY (Polyester Texture Yarn) manufacturer and has laid solid foundation on synthetic fibers after various expansions and diversifications with the united strength of all colleagues over the last 3 decades or so. In order to expand room for operations in the increasingly competitive environment, the enterprise has devoted to the pursuit of higher quality and steady growth. Because of the great competition in the market, an enterprise should know what clients need. TRI Ocean must develop new products in time to cater to customers and compete in the market. Although TRI Ocean has good competitive advantage in textile industry, duo to poor coordination among the departments of the company leads to huge losses since 2004. Until now, the company has not yet recovered from the losses. The company planned to install the new Polypropylene Filament Yarn equipment could be installed before September 2004. However, it was delayed due to the mismatch between the computer program and production need. This delay has seriously affected sales in the fourth quarter in 2004. Moreover, the test stage of the new equipment led to a halt in operation. Because of this, the management of TRI Ocean should have new strategies to save this company. TRI Ocean should improve its internal management by coordination between departments of company. Because TRI Ocean doesn't have downstream textile production, the company should adopt strategic alliance to improve competitive and increase sales. In order to confront the threat of ASEIAN Plus Three, TRI Ocean should more invest more in ASEIAN countries to decrease this threat in the future. The implementation of these strategies will strengthen the company's competencies and technological development in order to compete in the global market.